Ikhtibār Mi’yār al-Kafā’ah fī al-Lugah al-ʽArabiyyah bi-Mutașaffiḥ al-Imtiḥān al-Āmin fī Jāmiʽah Walisongo al-Islāmiyyah al-Ḥukūmiyyah Semarang - Inayah Inayah; Muhammad Ahsanul Husna; Uril Bahruddin; Fina Saadah; Muhammad Atif Audl Ramadlan (LISANIA: Journal of Arabic Education and Literature, 2023)
The objectives of the study include: 1. Describe the IMKA test with Safe Exam Browser (SEB), 2. Know the success rate achieved in the test. The research method used is qualitative descriptive analysis, data was collected in the form of observation, interviews, documentation, and triangulation combinations. Spradley model data analysis consists of domain analysis (categorization), taxonomic analysis (category elaboration), and componential analysis (looking for specific differences). The research time is divided into pre, implementation, and post. Pre-research in September 2021. The implementation is from September 2021 until the end of the online exam on August 8, 2022. Post is the time after the exam is over until the collection of the Language certificate. The primary sample/data source in this study is third and fifth-semester students from all departments and faculties within UIN Walisongo totaling 8,755 students with a schedule of 4 periods in July and 6 periods in August. The results showed that the IMKA Test with CBT type SEB has not shown the success of Arabic language skills in UIN Walisongo students, marked by a student graduation rate of 17.63% with the number of students graduating as many as 1,544 students.